2020
DOI: 10.1073/pnas.1911458117
|View full text |Cite
|
Sign up to set email alerts
|

Shale gas development has limited effects on stream biology and geochemistry in a gradient-based, multiparameter study in Pennsylvania

Abstract: The number of horizontally drilled shale oil and gas wells in the United States has increased from nearly 28,000 in 2007 to nearly 127,000 in 2017, and research has suggested the potential for the development of shale resources to affect nearby stream ecosystems. However, the ability to generalize current studies is limited by the small geographic scope as well as limited breadth and integration of measured chemical and biological indicators parameters. This study tested the hypothesis that a quantifiable, sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 64 publications
(91 reference statements)
3
16
1
Order By: Relevance
“…The RDP taxon Spartobacteria genera incertae sedis, which is relatively abundant in the Baltic Sea (Herlemann et al, 2016), was mapped to NCBI class Spartobacteria. The RDP taxon Subdivision3 genera incertae sedis, which was identified here in some stream datasets (Mumford et al, 2020) was mapped to NCBI family Verrucomicrobia subdivision 3. The RDP taxon Marinimicrobia genera incertae sedis, which was identified in this study in some deep ocean datasets (Ganesh et al, 2015;Meier et al, 2017), was mapped to NCBI species Candidatus Marinimicrobia bacterium, which is the only representative of the Candidatus Marinimicrobia phylum in the RefSeq database.…”
Section: Taxonomy Mappingmentioning
confidence: 99%
“…The RDP taxon Spartobacteria genera incertae sedis, which is relatively abundant in the Baltic Sea (Herlemann et al, 2016), was mapped to NCBI class Spartobacteria. The RDP taxon Subdivision3 genera incertae sedis, which was identified here in some stream datasets (Mumford et al, 2020) was mapped to NCBI family Verrucomicrobia subdivision 3. The RDP taxon Marinimicrobia genera incertae sedis, which was identified in this study in some deep ocean datasets (Ganesh et al, 2015;Meier et al, 2017), was mapped to NCBI species Candidatus Marinimicrobia bacterium, which is the only representative of the Candidatus Marinimicrobia phylum in the RefSeq database.…”
Section: Taxonomy Mappingmentioning
confidence: 99%
“…They found significant positive relationships between As concentration in streams and UOG well density but the mechanism of mobilization was not identified. Mumford et al (2020), however, found no statistically significant relationship between the intensity, presence, or absence of shale gas development and any signal in a comprehensive set of chemical constituents, including As, in their study of 25 small PA state forest watersheds over the course of 2 years. In another large-scale study of water quality data from PA watersheds, Olmstead et al (2013) also found that the presence of shale gas wells upstream from a particular watershed did not result in increased Cl concentrations downstream; however, the release of treated wastewater from shale gas wells by permitted wastewater treatment plants did appear to influence stream Cl concentrations.…”
Section: Arsenic In Drinking Water/stream Water From Oil and Gas Productionmentioning
confidence: 92%
“…Details on the materials released, volumes, and durations of spill events remain sparse, thus precluding the comprehensive assessment of groundwater contamination risks and potential public health implications [35]. Produced waters typically contain high concentrations of B, Ba, Br, Ca, Cl, Li, Na, Ra, and Sr, and hence their co-occurrence at anomalously elevated concentrations in shallow groundwater may be a useful indicator of contamination by UD [36][37][38][39]. Organic chemicals used in hydraulic fracturing fluid additives and derived from hydrocarbonbearing formations are also present in UD wastewaters and have been detected in groundwaters near UD sites [40][41][42][43][44][45].…”
Section: Background: Groundwater Quality In the Context Of Unconventional Oil And Gas Developmentmentioning
confidence: 99%